Accumulation of tissue inhibitor of metalloproteinases-3 in human eyes with Sorsby's fundus dystrophy or retinitis pigmentosa. Issue 11 (1st November 1998) - Fariss, Robert N; Apte, Suneel S; Luthert, Philip J; Bird, Alan C; Milam, Ann H
Abstract : BACKGROUND/AIMS: Tissue inhibitor of metalloproteinases-3 (TIMP-3) is normally synthesised by the retinal pigment epithelium (RPE) and deposited in Bruch's membrane. Mutations in the TIMP3 gene cause Sorsby's fundus dystrophy (SFD), which is characterised by thickening of Bruch's membrane, choroidal neovascularisation, and photoreceptor degeneration. To elucidate the role of TIMP-3 in human retinal degenerative diseases, we immunolocalised TIMP-3 in eyes with SFD caused by the Ser-181-Cys TIMP3 gene mutation or retinitis pigmentosa (RP; not caused by TIMP3 mutations). METHODS: Standard light microscopic immunocytochemistry, including antigen retrieval, was used to localise TIMP-3 in paraffin sections of human eyes: two with SFD, three with different genetic forms of RP, and two normal. RESULTS: In the SFD eyes, the thickened Bruch's membrane was strongly TIMP-3 positive except where RPE cells had degenerated. Similarly, in the RP eyes, Bruch's membrane was TIMP-3 positive except where RPE cells were lost, consistent with ongoing RPE mediated turnover of TIMP-3 in this region. In areas of total photoreceptor loss, migrated RPE cells formed cuffs around blood vessels in the RP retinas. Thick, TIMP-3 positive extracellular matrix (ECM) deposits associated with the migrated RPE cells occluded some vascular lumina, correlating with the observed loss of inner retinal neurons in RP. CONCLUSIONS: TIMP-3 is a component of the increased ECM sequestered in Bruch's membrane in SFD. Further information is needed on normal TIMP-3/ECM interactions in Bruch's membrane and the effect of mutant TIMP-3 on this process. The finding of TIMP-3 accumulations in retinas with RP not caused by TIMP-3 mutations emphasises the importance of ECM remodelling in normal and diseased human eyes.